Impact of Nepal-India Relations on Arun III Hydroelectric Project Implementation - Rai, Viswa (Kutumbha vani, 2024)
The Arun III Hydroelectric Project, Nepal's largest hydropower enterprise, is a cornerstone of Nepal-India bilateral ties, demonstrating the intricate interaction of energy diplomacy, political dynamics, and economic cooperation. This paper investigates how these bilateral ties have impacted the implementation of the Arun III project, from its inception to its current evolution. It examines the historical framework of Nepal-India interactions, including political agreements, economic interdependence, and regional geopolitics, which have influenced the project's progress. The article also discusses the obstacles that have hampered the project's timely completion, such as border conflicts, economic blockades, and changes in political leadership. It also looks at the opportunities that come with effective partnership, with a focus on energy commerce and sustainable development in South Asia. This paper, using international relations theory and detailed case studies, provides a comprehensive understanding of how bilateral relations between Nepal and India have shaped the Arun III project's trajectory, as well as insights into the broader implications for cross-border infrastructure development in the region.